2009
DOI: 10.1248/yakushi.129.523
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of JAK-2 in Attenuated Cardioprotective Effect of Ischemic Preconditioning in Hyperhomocysteinemic Rat Hearts

Abstract: The present study investigated the possible role of Janus kinase-2 (JAK-2) in hyperhomocysteinemia-induced attenuation of the cardioprotective eŠects of ischemic preconditioning (IPC). Rats were administered L-methionine (1.7 g/kg/day, p.o.) for 4 weeks to produce hyperhomocysteinemia. Isolated LangendorŠ's perfused normal and hyperhomocysteinemic rat hearts were subjected to global ischemia for 30 min, followed by reperfusion for 120 min. Myocardial infarct size was assessed macroscopically using triphenyltet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…The extent of CK-MB elevation strongly correlates with infarct size; moreover, LDH raises in myocardial infarction after reperfusion, which may be due to sustained ischemic injury (7). In the present study, 30 minutes ischemia followed by 60 min reperfusion produced myocardial injury as shown by elevated levels of CPK, CK-MB, and LDH in the coronary effluent, which was consistent with the earlier reports (21, 22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extent of CK-MB elevation strongly correlates with infarct size; moreover, LDH raises in myocardial infarction after reperfusion, which may be due to sustained ischemic injury (7). In the present study, 30 minutes ischemia followed by 60 min reperfusion produced myocardial injury as shown by elevated levels of CPK, CK-MB, and LDH in the coronary effluent, which was consistent with the earlier reports (21, 22).…”
Section: Discussionmentioning
confidence: 99%
“…In this process, free radicals steal electron from the lipids in cell membrane and result in cell damage (7). TBARS are low-molecular end products, the major component of which is MDA, that are made during the decomposition of lipid peroxidation product.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we showed that the cardioprotective potential of IPost did not occur in hearts from hyperhomocysteinemic rats (Dreiseitel et al, 2009;Rohilla and Balakumar, 2009;Singh et al, 2009;Rohilla et al, 2010). Mechanistically, a high degree of oxidative stress in hyperhomocysteinemic rat hearts in response to I/R injury may be responsible for the attenuated effects of IPost (Dreiseitel et al, 2009;Rohilla and Balakumar, 2009;Singh et al, 2009;Rohilla et al, 2010). Clearly, further studies are waranted to understand the modulatory role of various metabolic disorders in postconditioning-mediated myocardial protection.…”
Section: Factors Affecting Myocardial Post-conditioningmentioning
confidence: 99%
“…In conclusion it is reported that closure of K ATP channel and activation of JAK-2 may be responsible for abrogated cardio protective potential of IPC against I/R induced myocardial injury. 64 …”
Section: Impact Of Hyperhomocysteinemia On Ischemic Preconditioning Amentioning
confidence: 99%